Symposium 12: Information Society Studies in Practice - a Networked Learning Case Study: student needs and feedback in the NETIS project - Sadler, Chris; Kalvet, Tarmo (Proceedings of the International Conference on Networked Learning, 2008)
The Network for Teaching Information Society (NETIS) consortium has designed an Information Society studies curriculum aimed at university undergraduates. Courses can be delivered in various pedagogic formats including (appropriately) networked learning. NETIS has consulted students prior to developing this curriculum and trialled the learning materials in different contexts. Between January and March 2007 an online questionnaire was administered to students at a number of NETIS partner institutions. 492 students provided responses. As most useful sources of information students considered the Internet (53% of students listed it as their first or second choice) followed closely by the recommended course textbooks (52%). Surprisingly, only 32% listed their teachers as first or second choice and (more surprisingly) 21% listed teachers as the least favourite. Although the majority (60%) chose a course of conventional lectures supported by online materials (blended learning) as preferred learning style, fully a quarter of the students opted solely for the conventional lecture course. Only 4% would prefer an online-only course. When asked about preferred offline resources, students opted overwhelmingly (80%) for lecture notes or a dedicated textbook as opposed to more general library or other resources. About half of the student sample reported that they had already taken an Information Society course although there was the widest national variation here with 82% of Hungarian students having taken such a course, but only 11% of the United Kingdom students. However, 56% of all students claimed to have an interest in the topic and 80% thought that a textbook on the topic would be desirable. 60% of the students wanted a printed copy of the material in addition to access to an online format (20% were only interested in a printed version). In sum, e-learning 1.0 (traditional lectures supplemented by the online learning materials) fits with the declared study preferences of the majority of our student sample, who are happy to use online resources to supplement the physical learning environment comprising face-to-face contact with lecturers and printed materials. Although little enthusiasm was shown for the characteristic features of e-learning 2.0, it was tested in the teaching at some centres that started in September 2007. The experience shows that NETIS has designed an Information Society studies course which is suitable to a wide range of university undergraduate students. Although preliminary enquiries about students’ preferred learning styles was not very encouraging, it turns out that students can embrace this pedagogy with some enthusiasm, provided that the teachers are willing to put in the effort. In one of the teaching locations the students made extensive use of the interactive tools. They seemed to enjoy engaging in knowledge creation and enthusiastically monitored the growth of entries in the course dictionary. It was clear that they enjoyed sharing solutions with other students and groups and that they learned from this sharing. Another university plans to try an entirely e-learning course with students in sociology and then to compare results with the group that used more traditional approaches.